Bacteria as Nanoparticles Carrier for Enhancing Penetration in a Tumoral Matrix Model. Issue 11 (21st April 2020) - Moreno, Víctor M.; Álvarez, Elena; Izquierdo‐Barba, Isabel; Baeza, Alejandro; Serrano‐López, Juana; Vallet‐Regí, María
Abstract: One of the major concerns in the application of nanocarriers in oncology is their scarce penetration capacity in tumoral tissues. Living organisms (cells and bacteria) present the capacity to navigate autonomously following chemical gradients being able to penetrate deeply into dense tissues. Currently, the possibility to employ these organisms for the transportation of therapeutic agents or nanocarriers has received huge attention. Herein, a new approach to deliver drug‐loaded nanoparticles achieving high penetration in tumoral matrices is presented. Escherichia coli bacteria wall is decorated with azide groups, whereas alkyne‐strained groups are incorporated on the surface of mesoporous silica nanoparticles loaded with a potent cytotoxic compound, doxorubicin. Both functional groups form stable triazole bonds by click‐type reaction allowing the covalent grafting of nanoparticles on living bacteria. Both motility and penetration capacity are evaluated in a 3D tumoral matrix model composed by a dense collagen extracellular matrix containing human fibrosarcome cells. The results confirm that bacteria are able to transport the nanoparticles crossing a thick collagen layer being able to destroy almost 80% of the tumoral cells located underneath. These findings envision a powerful strategy in cancer treatment by allowing a homogeneous distribution of therapeutic agents in the malignancy. Abstract : Bacteria‐assisted mesoporous silica nanoparticles achieve high penetration in tumor matrix models. The motility of bacteria allows the delivery of cytotoxic drugs into deep areas of the malignancy, improving their therapeutic effect in comparison with free nanoparticles.